2005
DOI: 10.1083/jcb.200409067
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3 is an endogenous inhibitor of Snail transcription

Abstract: We report that the activity of glycogen synthase kinase-3 (GSK-3) is necessary for the maintenance of the epithelial architecture. Pharmacological inhibition of its activity or reducing its expression using small interfering RNAs in normal breast and skin epithelial cells results in a reduction of E-cadherin expression and a more mesenchymal morphology, both of which are features associated with an epithelial–mesenchymal transition (EMT). Importantly, GSK-3 inhibition also stimulates the transcription of Snail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
299
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(327 citation statements)
references
References 24 publications
23
299
3
2
Order By: Relevance
“…Previously, Monaghan et al showed distinct and elevated expression patterns of DKK-1, -2 and -3 in tissues that mediate epithelialmesenchymal transformations and suggested that they participate in the process of EMT (Monaghan et al, 1999). Additionally, regulation of snail expression and activity by Wnt could be shown (Laux et al, 2004;Bachelder et al, 2005;Yook et al, 2005). These data is supported by our findings that snail-1 expression is downregulated after expression of DKK-3.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, Monaghan et al showed distinct and elevated expression patterns of DKK-1, -2 and -3 in tissues that mediate epithelialmesenchymal transformations and suggested that they participate in the process of EMT (Monaghan et al, 1999). Additionally, regulation of snail expression and activity by Wnt could be shown (Laux et al, 2004;Bachelder et al, 2005;Yook et al, 2005). These data is supported by our findings that snail-1 expression is downregulated after expression of DKK-3.…”
Section: Discussionsupporting
confidence: 89%
“…As Snail alone does not induce nuclear localization of bcatenin, coinduction of Snail and Wnts by Gli1 may synergize to switch b-catenin from cell adhesion to nuclear signaling. Wnt signaling to GSK3b can further promote Snail transcription and stabilize the protein (Zhou et al, 2004;Bachelder et al, 2005;Yook et al, 2005). Snail promoted expression of Gli1 in our studies, probably by a post-transcriptional mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…GSK3b acts in the Wnt pathway but also regulates Hedgehog signaling, including the Gli1-target gene Snail (Zhou et al, 2004;Bachelder et al, 2005;Yook et al, 2005;Price, 2006). Wnt and Shh signals play distinct roles in the development of hair follicles in the skin (Alonso and Fuchs, 2003;Silva-Vargas et al, 2005;Brembeck et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-b increases Snail expression during hair bud morphogenesis (37), while Notch upregulates Snail during cardiac valve development (38). Studies with cultured cells have identified several intracellular signaling pathways capable of inducing Snail transcription, including the MAPK, phosphoinositide-3-kinase (PI3K), integrinlinked kinase (ILK), and nuclear factor-kB (NFkB) pathways (39)(40)(41)(42). Several transcription factors have been linked to Snail induction, including Gli1 (43), early growth response 1 (EGR1; ref.…”
Section: Discussionmentioning
confidence: 99%
“…Other signaling pathways implicated in EMT, including Wnt and phosphoinositide 3-kinase (15,16), use GSK-3 to mediate their responses. GSK-3 is an endogenous inhibitor of Snail transcription (17) and GSK-3b mediated phosphorylation of Snail has been shown to facilitate its proteasomal degradation (18). Low oxygen induces Snail transcription (19)(20)(21)(22) and both the canonical HIF (22,23) and Notch (24,25) pathways have been implicated in hypoxia-induced EMT.…”
Section: Introductionmentioning
confidence: 99%